Micro Enterprises – An unseen entity in public procurement policy - Davis, Paul; McKevitt, David; Flynn, Anthony (Piccola Impresa / Small Business, 2013)
Small and Medium Size Enterprises have been the subject of much scholarly research. There has however little attention been paid to the influence of size within the SME sector to the success of organisations winning public sector contracts. Micro-enterprises which make up over 50 % of the SME sector in Europe are not seen as a separate sector and as such public policy has lapsed in focusing on these enterprises. This paper builds on the scholarly work that has taken place on SME’s and adds empirical evidence, firstly by describing the makeup of the public sector supply market and secondly by examining the relationship between size and success in public sector tendering. The paper explores two cross sectional survey encompassing over 4000 supplier responses for both surveys and analyses the first survey for statistical evidence of the influence of size on public sector tendering. We draw the conclusion that the research to date has not focused on the main sector of microenterprises and that they are in fact the unseen entity in public procurement policy.